Molecules from Side Reactions - D'Errico, Stefano (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The Special Issue "Molecules from Side Reactions" is a collection of papers reporting on the synthesis and characterization of the molecules that come from unexpected synthetic routes. This is the first example of a Special Issue based on such a topic, notwithstanding that all synthetic chemists have isolated a side product during a chemical reaction. Instead of continuing to store the side products in the freezer, I have thought to give them the dignity of publication, making them available to the scientific community. The short manuscripts collected here respect the principle of "one compound per paper" and have the purpose of preserving the molecular diversity deriving from a chemical reaction. The molecular scaffolds are unexpected and intriguing, and could be useful starting points or intermediates for exploring novel reactions.